Character's theater : genre and identity on the eighteenth-century English stage - Freeman, Lisa A. (University of Pennsylvania Press, 2002)
"Lisa Freeman's excellent cultural analysis ... demonstrates that character is a contested site in England's attempt to negotiate a changing sociology of class, gender, and nation even as it retained fundamental forms of patriarchy."--Albion